Penguatan Keterampilan Sosial Siswa Sekolah Dasar di Era Digital - Indah; Alpian, Yayan; Maria Dewi, Sinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the condition of elementary school students' social skills in the digital era. The research employed a qualitative approach using a phenomenological method. The participants consisted of a fourth-grade teacher and 28 fourth-grade students. Data were collected through participant observation, in-depth interviews, questionnaires, and documentation. The data were analyzed using the Miles and Huberman model. The findings revealed that students' social skills had not developed optimally, as indicated by weakened face-to-face social interactions, low self-confidence in direct communication, less effective collaboration, declining empathy, and weak self-control in the use of digital devices. The dominance of smartphone use emerged as the main inhibiting factor, while teachers' roles, parental support, and a conducive school environment served as supporting factors in the development of students' social skills. Therefore, strengthening social skills in the digital era requires synergy between schools and families through adaptive learning practices and more responsible and purposeful use of technology.